2011
DOI: 10.1007/s00702-011-0718-2
|View full text |Cite
|
Sign up to set email alerts
|

Administration of memantine and imipramine alters mitochondrial respiratory chain and creatine kinase activities in rat brain

Abstract: Several studies have appointed for a role of glutamatergic system and/or mitochondrial function in major depression. In the present study, we evaluated the creatine kinase and mitochondrial respiratory chain activities after acute and chronic treatments with memantine (N-methyl-D: -aspartate receptor antagonist) and imipramine (tricyclic antidepressant) in rats. To this aim, rats were acutely or chronically treated for 14 days once a day with saline, memantine (5, 10 and 20 mg/kg) and imipramine (10, 20 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
(97 reference statements)
2
12
0
Order By: Relevance
“…Furthermore, 4-methyl-2-oxopentanoate is often used to assess liver mitochondrial function and can influence glutamate synthesis in neurons [80, 81]. Several studies have implicated alterations in brain energetics in the pathogenesis of depression and effects of antidepressants [38, 82, 83]. Consistent with these observations, our results suggest a model in which subtle alterations in mitochondrial bioenergetics may contribute to the pathophysiology of depressive symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, 4-methyl-2-oxopentanoate is often used to assess liver mitochondrial function and can influence glutamate synthesis in neurons [80, 81]. Several studies have implicated alterations in brain energetics in the pathogenesis of depression and effects of antidepressants [38, 82, 83]. Consistent with these observations, our results suggest a model in which subtle alterations in mitochondrial bioenergetics may contribute to the pathophysiology of depressive symptoms.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, a study by Assis et al (2009) showed that the acute administration of ketamine, besides producing an anti-immobility effect, increased the creatine kinase activity in striatum, cerebral cortex and cerebellum. Memantine, another NMDAR antagonist with anti-immobility effect, also increased creatine kinase activity in prefrontal cortex and hippocampus of rats (Reus et al 2012). In vitro and in vivo studies have reported that ketamine and MK-801 facilitate recovery of phosphocreatine levels after ischemic or anoxic brain injury, clinical conditions associated with glutamatergic dysfunction (Bielenberg et al 1987;Haraldseth et al 1990;Raley and Lipton 1990;Spandou et al 1999).…”
Section: Discussionmentioning
confidence: 97%
“…In the case of mixed or dual uptake inhibitors, four weeks of either clomipramine (Anafranil) or tianeptine (Stablon) have been shown to normalize total creatine in the forebrain of stressed tree shrews (Czéh et al, 2001; Fuchs et al, 2002; van der Hart et al, 2002), four weeks of desipramine (Norpramine) increased total creatine in the DLPFC of male C57BL/6 mice (Kim et al, 2010), and acute imipramine (Tofranil) increased creatine kinase activity in the striatum, cerebellum, and PFC of rats (Assis et al, 2009; Réus et al, 2011, 2012). For atypical antipsychotics, acute treatment with aripiprazole (Abilify) or olanzapine (Zyprexa) increased creatine kinase activity in the striatum and cerebellum (Assis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%